Anastomosing hemangioma of the kidney: a case report - Lazić, Aleksandar; Marić, Predrag; Tadić, Jelena; Kovačević, Božidar; Jovanović, Bojana; Krća, Bojana; Mijušković, Mirjana (Vojnosanitetski pregled, 2025)
Introduction. Renal anastomosing hemangioma (AH) is a very rare vascular tumor. This type of tumor is named so because of its unique histological structure, which resembles splenic sinusoidal structures. It may mimic malignant neoplasms, like angiosarcoma, which is why clinical and radiological examinations are insufficient for accurate diagnosis. Case report. We present a case of a 39-year-old male admitted to the Clinic for Nephrology at the Military Medical Academy, Belgrade, Serbia, for considering a living-related kidney transplant due to the development of end-stage renal disease (ESRD). His father was identified as the prospective donor. During the patient’s pre-transplant evaluation, a suspect tumorous lesion in the left kidney was observed, and multislice computed tomography scanning of the abdomen and small pelvis was performed. This imaging revealed a lobulated soft tissue lesion measuring approximately 25 × 15 mm in the lower pole of the left kidney. Based on this finding, it was decided to proceed with a left nephrectomy to obtain a histopathological assessment of the lesion. The histopathological examination, complemented by immunophenotyping, led to the diagnosis of an AH in the kidney. Conclusion. The presented case emphasizes the importance of urgent surgical resection of the tumor mass in order to confirm the diagnosis and avoid any delay in patients scheduled for kidney transplantation.
Keywords: diagnosis, differential; hemangioma; immunohistochemistry; kidney failure, chronic; kidney transplantation; multidetector computed tomography; vascular neoplasms.